(untitled) (TẠP CHÍ Y DƯỢC THÁI BÌNH, 2024)
Objective: To describe the clinical, subclinical characteristics and surgical outcomes of uterine fibroids at Thai Binh Medical University Hospital. Method: The study described through a cross-sectional survey of 250 patients diagnosed with uterine fibroids and operated at Thai Binh Medical University Hospital from 01/01/2020 to 31/12/2023. Result: The median age of patients with uterine fibroids was 46.04 ± 5.97. There were 44.82% of patients with uterine fibroids because of abdominal pain, 52.37% went to the doctor because of menstrual bleeding. Unusual uterine morphology, including a patient-detected mass, was observed in some cases. There were 1.2% of patients with uterine fibroids with signs of mild and moderate anaemia, and there were no cases of blood transfusions before or after surgery. Patients indicated for planned surgery accounted for 93.6%, the mean fibroid size was 5.44 ± 2.34 cm, and the most common surgical procedure was open myomectomy (87.2%), with there were no intraoperative complications or postoperative complications. Conclusion: Based on the results, it can be concluded that women with uterine fibroids are typically in middle age (average age 46 years), with the most common clinical symptom being lower abdominal pain. The majority of patients presented with mild anemia and were commonly treated with open surgery, with an average hospital stay of approximately 6.5 days. Notably, no complications were recorded.